Using a TAM-TOE model to explore factors of Building Information Modelling (BIM) adoption in the construction industry - Qin, Xuan; Shi, Ye; Lyu, Kuncan; Mo, Yiyi (Journal of Civil Engineering and Management, 2020)
Building Information Modelling (BIM) has been adopted as the main technology in the construction industry in many developed countries due to its notable advantages. However, its applications in developing countries are limited. This paper aims to investigate factors which impact on BIM adoption in the construction industry. Twelve external variables were identified by an integrated TAM (Technology Acceptance Model) and TOE (Technology Organization Environment) framework and a systematic review of past studies. A survey was conducted in development, construction, design and consulting companies to investigate the impacts of these 12 external variables on BIM adoption. Using the interval Decision Making Trial and Evaluation Laboratory (DEMATEL) method, retrieved 120 completed questionnaires were analysed. The “Requirements from national policies” was found to be the most significant driving variable of BIM adoption by investigated companies. A further simulation analysis revealed that the “Intention to Use” BIM varied significantly with the change of “Requirements from national policies”, “Standardization of BIM”, and “Popularity of BIM in the industry”. The results lead to the conclusion that government incentives play critical roles in BIM adoption in China. Policy makers could put more efforts into motivation strategies, standardization measures, and BIM culture cultivation to promote BIM applications in the construction industry.